A method for the tin pest presence testing in SnCu solder alloys. Issue 3 (27th May 2014) - Skwarek, Agata; Kulawik, Jan; Czerwinski, Andrzej; Pluska, Mariusz; Witek, Krzysztof
<x content-type="archive" xml:space="preserve">Abstract</x> Purpose – The purpose of this study is to develop a testing method for tin pest in tin – copper (SnCu) alloys. Tin pest is the allotropic transformation of white β-tin (body-centered tetragonal structure) into gray α-tin (diamond cubic structure) at temperatures < 13.2°C. Design/methodology/approach – Bulk samples of Sn99Cu1 weight per cent (purity, 99.9 weight per cent) were cast in the form of roller-shaped ingots with a diameter of 1.0 cm and a height of 0.7 cm. The samples were then divided into four groups. The first group included samples artificially inoculated with α-tin powder. The second group was inoculated in the same way as the samples from the first group but additionally subjected to mechanical pressing. The third group of ingots was only subjected to mechanical pressing. The fourth group of samples consisted of as-received roller-shaped ingots.All samples were divided into two groups and kept either at −18°C or at −30°C for the low-temperature storage test. For tin pest identification, a visual inspection was made, using a Hirox digital microscope over 156 days at intervals not longer than 14 days. The plot of the transformation rate, presented as the average increase in the area of α-tin warts in time, was also determined. To demonstrate the differences between regions of β- and α-tin, scanning ion microscopy observations using the focused ion beam technique was performed. Findings – The first symptoms of tin pest were observed for the inoculated, mechanically pressed samples stored at −18°C, as well as those at −30°C, after less than 14 days. In the first stage of transformation, the rate was higher at −30°C for some time but, after about 75 days of storage at sub-zero temperatures, the rate at −30°C became lower compared to the rate at −18°C. Inoculation via the application of substances which are structurally similar to α-tin was efficient for the proposed new approach of rapid testing only when applied with simultaneous mechanical pressing. Infection from pressed-in seeds, leading to conventional seeded growth, was more rapid than infection in contact with seeds (without mechanical pressing), where the transition mechanism was induced by the epitaxial growth of metastable ice. Originality/value – The new rapid method for the diagnostic testing of the susceptibility of different SnCu alloys to tin pest in a period much shorter than 14 days (within single days for storage at −30°C) is proposed and described. The test procedure described in this paper produced results several times quicker than conventional procedures, which may take years. In effect, the behavior of tin alloys in the face of tin pest may be predicted much more easily and much earlier. The same procedure can be applied to other SnCu alloys used in electronics (and in other areas), if the test samples are prepared in a similar manner.